Sciences of Geodesy - II Innovations and Future Developments - Xu, Guochang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This series of reference books describes the sciences of different fields in and around geodesy. Each chapter, is written by experts in the respective fields and covers an individual field and describes the history, theory, the objective, the technology, and the development, the highlight of the research, the applications, the problems, as well as future directions. Contents of Volume II include: Geodetic LEO Satellite Missions, Satellite Altimetry, Airborne Lidar, GNSS Software Receiver, Geodetic Boundary Problem, GPS and INS, VLBI, Geodetic Reference Systems, Spectral Analysis, Earth Tide and Ocean Loading Tide, Remote Sensing, Photogrammetry, Occultation, Geopotential Determination, Geoid Determination, Local Gravity Field, Geopotential Determination, Magnet Field, Mobile Mapping, General Relativity, Wide-area Precise Positioning etc.
Geodetic LEO Satellite Missions -- Satellite Altimetry -- Airborne Lidar -- GNSS Software Receiver -- Geodetic Boundary Problem -- GPS and INS -- VLBI, Geodetic Reference Systems -- Spectral Analysis -- Earth Tide and Ocean Loading Tide -- Remote Sensing -- Photogrammetry -- Occultation -- Geopotential Determination -- Geoid Determination -- Local Gravity Field -- Geopotential Determination -- Magnet Field -- Mobile Mapping -- General Relativity -- Wide-area Precise Positioning etc.
Keywords: Geography; Physical geography; Geographical information systems; Earth Sciences; Geophysics/Geodesy.; Geophysics and Environmental Physics; Geographical Information Systems/Cartography.